Kualitas Pelayanan Di Balai Pelatihan Dan Pengujian Keselamatan Kerja Dan Hiperkes (BPPKK dan Hiperkes) Provinsi Jawa Tengah - Nico Putra Triwibowo; Ida Hayu Dwimawanti (Journal of Public Policy and Management Review, 2018)
This research is intended to analyze the quality of services provided by the Office of Training and Testing of Work Safety and Hyperkes against the company and analyze the factors that inhibit the service at the office. To meet the intended purpose, the descriptive method with qualitative approach techniques using five (5) dimensions of service quality as an indicator in assessing service quality are tangibles, assurance, reliability, (responsiveness), and empathy (emphaty). The results showed that the quality of service at BPPKK office and hyperkes in general have been good, seen from physical evidence (tangibles) condition of building and laboratory room at this time its capacity not in accordance with standard set by government. In terms of facilities and infrastructure, some equipment is still good. But as the development of science and technology has not been sufficient both in terms of quality and quantity. Employees use uniforms according to the schedule specified .. Reliability (realibility) results both in terms of data accuracy as supported by the ability of human resources and accredited laboratories and equipment that is calibrated just the speed and timeliness of testing has not been satisfactory as well as the delivery of test results report (LHU ) sometimes not on time. Assurance (assurance) results are well reviewed from the skills, knowledge, skills and knowledge of employees. Responsiveness (responsiveness) and empathy (emphaty) is good. While the factors that hinder the quality of service 1) the awareness of the officer will be less time discipline, 2) The time certainty is not fully in accordance with SOP, due to lack of alignment between front office and back office 3) lack of knowledge owned by the community related to the completeness of requirements. And the responsiveness of the community is still lacking when there are less requirements that are not immediately completed